A seven country comparison of nurses' perceptions of their professional practice environment - PAPASTAVROU, EVRIDIKI; EFSTATHIOU, GEORGIOS; ACAROGLU, RENGIN; DA LUZ, MARIA DEOLINDA ANTUNES; BERG, AGNETA; IDVALL, EWA; KALAFATI, MARIA; KANAN, NEVIN; KATAJISTO, JOUKO; LEINO-KILPI, HELENA; LEMONIDOU, CHRYSSOULA; SENDIR, MERDIYE; et al. (Journal of nursing management, 2012)
Papastavrou E., Efstathiou G., Acaroglu R., da Luz M.D.A., Berg A., Idvall E., Kalafati M., Kanan N., Katajisto J., Leino‐Kilpi H., Lemonidou C., Sendir M., Sousa V.D. & Suhonen R. (2012) Journal of Nursing Management20, 236–248  A seven country comparison of nurses’ perceptions of their professional practice environment Aims  To describe and compare nurses’ perceptions of their professional practice environment in seven countries. Background  There is evidence of variation in the nursing professional practice environments internationally. These different work environments affect nurses’ ability to perform and are linked to differing nurse and patient outcomes. Methods  A descriptive, comparative survey was used to collect data from orthopaedic and trauma nurses (n = 1156) in Finland, Cyprus, Greece, Portugal, Sweden, Turkey and Kansas, USA using the 39‐item Revised Professional Practice Environment instrument. Results  Differences were found between participants from the northern countries of Europe, Kansas, USA, and the Mediterranean countries regarding perceptions about control over practice. No between‐country differences were reported in the internal work motivation among the nurses from any of the participating countries. Conclusions  Although between‐country differences in nurses’ professional practice environment were found, difficulties related to demographic, cultural and health system differences and the way in which nursing is defined in each country need to be considered in the interpretation of the results. Implications for Nursing Management  The results support investment to improve nurse’s work environment, which is important for improving the quality of patient care, optimizing patient outcomes and developing the nursing workforce.